Internet of Things Challenges and Opportunities - Mukhopadhyay, Subhas Chandra; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Advancement in sensor technology, smart instrumentation, wireless sensor networks, miniaturization, RFID and information processing is helping towards the realization of Internet of Things (IoT). IoTs are finding applications in various area applications including environmental monitoring, intelligent buildings, smart grids and so on. This book provides design challenges of IoT, theory, various protocols, implementation issues and a few case study. The book will be very useful for postgraduate students and researchers to know from basics to implementation of IoT.
Internet of Things: Challenges and Opportunities -- Exploring Major Architectural Aspects of the Web of Things -- Embedded Web Technologies for the Internet of Things -- High-Level Internet of Things Applications Development using Wireless Sensor Networks -- 6TiSCH Wireless Industrial Networks: Determinism Meets IPv6 -- Vehicular Ad Hoc Networks and Trajectory-based Routing -- Internet of Things Low-Cost Long-Term Environmental Monitoring with Reusable Wireless Sensor Network Platform -- A High Performance ROIC for a Standalone Monitoring System in IoT Environments -- Ambient Assisted Living Environment towards Internet of Things using Multifarious Sensors Integrated with XBee Platform -- Towards Autonomous Wireless Sensors: RFID and Energy Harvesting Solutions.
Keywords: Engineering; Computer science; Electronics; Telecommunication; Engineering; Communications Engineering, Networks; Electronics and Microelectronics, Instrumentation; Information Systems Applications (incl. Internet).; User Interfaces and Human Computer Interaction